Quality of life in dilated cardiomyopathy with refractory chronic heart failure undergoing devices implantation - Nave Leal, Elisabete (2012)
Heart failure is the final stage of most of cardiac diseases. It is a complex syndrome in which the patients should have the following features: symptoms of heart failure, typically shortness of breath at rest or during exertion, and/or fatigue; signs of fluid retention such as pulmonary congestion or ankle swelling; and objective evidence of an abnormality of the structure or function of the heart at rest. This progressive syndrome as a high incidence and prevalence and poor prognosis: four-year mortality is around 50% with 40% of the patients admitted to hospital dying or readmitted within a year. With ageing, many patients will develop chronic heart failure, which, because of its symptoms, patient’s awareness of their risk of dying, and the effects of therapy, together with frequent hospitalizations, has considerable impact on patient’s health-related quality of life.